PENGEMBANGAN SET PRAKTIKUM PEMBIASAN CAHAYA UNTUK PEMBELAJARAN FISIKA DI SMA - Arum Sri Rahayu; Vina Serevina; Raihanati Raihanati (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
This research aims to develop a set of practical work for 11th grade Senior High School at sub light refraction material. The method of the research is R & D (Research and Development) of Borg and Gall which is limited to four developmental stages: 1. Preliminary study, 2. Product development, 3. Validation and Product Revision, 4. Products trials. This research was conducted from January to May 2016 in FMIPA’s Physics Laboratory of State University of Jakarta. Set refraction of light has been through validity test involving matter experts that consist of physics lecturer and physics education lecturer with the percentage 95.01% according to matter experts, 94.14% according to media expert. The field test of this set conducted to 63 Senior High School students and three physics teachers at SMAN 58 Jakarta with the percentage of achievement 88.45% according to physics teacher and 80.58% according to Senior High School students. The results of the study showed the bent ray that pass through two different mediums and the angle deviation of light that used for determining the index refractions which passed by light using the Snellius’s equation. Based on this research, it can be summarized that the development of set refraction is useful for material physics at senior high school. Keywords: Set of Refraction ,Refractions, Index Refractions